Evolving cooperation in multichannel games - Kate Donahue (Nature Portfolio, 2020)
Most evolutionary game theory focuses on isolated games. Here, Donahue et al. present a general framework for ‘multichannel games’ in which individuals engage in a set of parallel games with a partner, and show that such parallel interactions favor the evolution of reciprocity across games.